1996
DOI: 10.1037/0012-1649.32.2.254
|View full text |Cite
|
Sign up to set email alerts
|

Are East Asian versus American differences in arithmetical ability a recent phenomenon?

Abstract: Younger and older American and Chinese adults were administered arithmetic, perceptual speed, and spatial orientation tests. For the perceptual speed and spatial orientation tests, the younger adults showed substantial performance advantages over the older adults in both the United States and China. For the arithmetic tests, the younger Chinese adults outperformed the older Chinese adults, but the groups of younger and older American adults had comparable arithmetical abilities. Cross-national comparisons indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
45
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 39 publications
8
45
0
Order By: Relevance
“…A more recent study supported the same conclusion (Geary, Salthouse, Chen, & Fan, 1996). Here, groups of comparably educated Chinese and American college students and older (57-to 85-year-old) adults were administered a battery ofpsychometric tests, including measures of computational arithmetic (e.g., 45 +83 + 19), perceptual speed (e.g., speed of reading numbers), and spatial abilities.…”
mentioning
confidence: 64%
“…A more recent study supported the same conclusion (Geary, Salthouse, Chen, & Fan, 1996). Here, groups of comparably educated Chinese and American college students and older (57-to 85-year-old) adults were administered a battery ofpsychometric tests, including measures of computational arithmetic (e.g., 45 +83 + 19), perceptual speed (e.g., speed of reading numbers), and spatial abilities.…”
mentioning
confidence: 64%
“…Previous studies excluded potential causes such as cognitive ability or intelligence (e.g., Geary, 1996a;Geary, Salthouse, et al, 1996). However, there is a variety of other explanations.…”
Section: Cultural Differences In Strategic Performancementioning
confidence: 99%
“…Interestingly, cultural differences in strategy efficiency have been shown in the domain of simple arithmetic. Asians solve simple arithmetic problems (e.g., 7 + 5) more quickly and accurately than North Americans (Campbell & Xue, 2001;Geary, 1996b;Geary, Bow-Thomas, Fan, & Siegler, 1993;Geary, BowThomas, Liu, & Siegler, 1996;Geary, Salthouse, Chen, & Fan, 1996;Geary et al, 1997;LeFevre & Liu, 1997;Penner-Wilger, Leth-Steensen, & LeFevre, 2002). This effect was, in part, a result of cultural differences in strategy selection: Asians retrieved the answers from long-term memory more frequently than North Americans, who were more inclined to use non-retrieval strategies Complex Arithmetic -6 such as transformation (e.g., 7 + 5 = 7 + 3 + 2 = 10 + 2 = 12) or counting (e.g., 7 + 2 = 7, 8, 9).…”
mentioning
confidence: 99%
“…Several studies found differences between East Asians' and North Americans' performance on simple arithmetic (see, e.g., Campbell & Xue, 2001;Chen & Uttal, 1988;Geary, 1996;Geary, BowThomas, Liu, & Siegler, 1996;Geary et al, 1997;Geary, Liu, & Bow-Thomas, 1992;Geary, Salthouse, Chen, & Liu, 1996;LeFevre & Liu, 1997;Penner-Wilger, LethSteensen, & LeFevre, 2002;Stevenson, Chen, & Lee, 1993;Stevenson et al, 1990;Stevenson, Lee, & Stigler, 1986). Because East Asians rely primarily on memory retrieval, their arithmetic performance is faster and less error prone than that of North Americans, who frequently use procedures.…”
Section: Individual Differencesmentioning
confidence: 99%